Analysis of Condom Use Behavior and Number of Sex Partners as Risk Factors for HIV/AIDS in the Group of Men Having Sex with Men in Kendari City Hospital - Appe, Samsu; Rahmawati, Rahmawati; Azizi Jayadipraja, Erwin (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Based on the results of observations, it shows that the majority of respondents engage in more unprotected anal sex and ejaculatory oral sex. This activity is mostly carried out by different sexual partners with a very regular frequency, which results in the transmission of HIV/AIDS. This is what is interesting for researchers to conduct research on Behavioral Analysis of Condom Use and Number of Sex Partners as Risk Factors for HIV/AIDS in the Group of Men Who Have Sex with Men at the Kendari City Regional Hospital. Method: This type of research is quantitative research with a case control research design. The case population in this study was 349 men with male sex with positive (+) HIV test results and 423 men with male sex with negative (-) HIV test results. The sample in this study was taken using a random sampling method, totaling 75 respondents using the Lemeshow formula. Result: Confidence Interval (CI) at the 95% confidence level with a lower limit value of 3.361 and an upper limit of 15.229. The OR value obtained shows that condom use is a risk factor with LL and UL values and Confidence Interval (CI) at the 95% confidence level with a lower limit value of 9.090 and an upper limit of 48.517. Conclusion: Condom use and number of sexual partners are behavioral risk factors for HIV/AIDS in the group of men having sex with men at the Kendari City Regional Hospital.